The influence of macroeconomic towards the number of IPO's in the Malaysian stock market / Abdul Muhaimin Sharil Goh - Sharil Goh, Abdul Muhaimin (2022)
This research is aiming to determine the amount of influence does various macroeconomic variables could influence the amount of companies going public and through IPO in Bursa Malaysia each year, analysing data from 1980 to 2020. The research was performed by taking data produced by Bursa Malaysia as well as other secondary data which are the Gross Domestic Product (GDP), Interest Rate (IR), Stock Market Performance (KLCI), and Inflation Rate (IFR). The data will be run through and analysed using multiple tests such as descriptive statistics, correlation, multiple regression tests, and more. The researcher may conclude from this research that there are correlation between the macroeconomic variables and the number of companies going public in Malaysia.